Tradition Paca Goya as a Symbol of Nature Conservation For the Tidore Community - Iksan Hasim; Putri Nurdiana Jailan (International Journal of Education, Information Technology, and Others, 2022)
This research is a response to the contribution or benefits of the Paca Goya to the preservation of Tidore's nature which is very large, because on the one hand the problem is the occurrence of natural damage due to ignorant human hands which of course greatly affects the balance of nature. This research also certainly has the goal of providing a stimulus to the community so that they maintain local traditions that have utility value for the community. development of tradition as local wisdom